A Study on the Developmental Features of Yi Students’ Chinese Mental Lexicon - Li, Ming; Zhang, Lubei; Zhou, Qi (Frontiers in Psychology, 2022)
Adopting free word association test, the present study investigated the developmental features of Yi students' Chinese mental lexicon. The subjects were divided into two groups: 80 primary school students and 85 senior high school students. The prompt words were 108 words commonly used in modern Chinese. The results showed that 1) The mental lexicon of Yi primary and middle school students were mainly connected with each other by meanings, with form-based connection followed. Compared with previous studies, their phonological associations accounted for a relatively higher proportion, while semantic associations were relatively weakened. 2) Syntagmatic associations were of primary importance, with paradigmatic and encyclopedic associations followed. 3) While syntagmatic relation was centered on determinative and governing associations, paradigmatic relation was dominated by adjacent and reverse associations. 4) The development rate of syntagmatic associations was faster than that of paradigmatic and encyclopedic associations; no significant improvement was found on students’ adjacent , layer, homogeneous and supplement associations from primary school to high school. The findings generate important implications for Yi students’ Chinese language education.